Reinforced microcrystalline glass, glass device and electronic equipment
Patent Information
- Application Number
- CN202380051849.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-06-30
- Publication Date
- 2025-04-15
AI Technical Summary
The existing glass-ceramics with lithium feldspar and lithium disilicate as the main crystal phases are deficient in resistance to non-contact surface cracking, and their chemical durability does not perform well in special environments, affecting its use effect.
By introducing a compressive stress layer and a tensile stress layer into the glass-ceramics, the ratio of the surface compressive stress (CS) and the average tensile stress (|CT_AV|) of the tensile stress layer is optimized, the surface K2O concentration is enhanced, and the grain size and composition are controlled. , forming a specific stress structure to improve the resistance to non-contact surface cracking and contact surface cracking, while improving weather resistance.
It has achieved a significant improvement in the resistance to non-contact surface cracking and contact surface cracking of the crystal-ceramic glass, and maintained excellent weather resistance in high temperature and high humidity environments, meeting the needs of electronic equipment covers.
Smart Images

Figure CN119836404A_ABST
Abstract
Description
Strengthened microcrystalline glass, glass device and electronic device
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This disclosure claims priority to Chinese patent application number CN202210869330.9, filed with the State Intellectual Property Office of China on July 22, 2022, and entitled “A Strengthened Microcrystalline Glass, Glass Device, and Electronic Device,” the entire contents of which are incorporated by reference into this disclosure. Technical Field
[0003] The present disclosure belongs to the technical field of lithium aluminum silicon microcrystalline glass, and specifically relates to a reinforced microcrystalline glass and glass devices and electronic equipment with excellent single-body strength and excellent drop resistance. Background Art
[0004] With the advent of the smart age, electronic devices such as mobile phones, tablets, and watches have become an indispensable part of daily life. Most of these devices are damaged by screen shattering, so the strength of cover glass needs to be improved urgently. Cover glass damage often occurs when a smartphone is dropped or impacted with another object. Generally speaking, there are two main types of damage: cracking on the contact surface and cracking on the non-contact surface.
[0005] Contact surface cracking refers to the situation where the glass surface is partially damaged when it collides with a sharp object with greater hardness (such as fine sand, cement, or pebbles), forming a hemispherical crack propagation source at the point of damage. The collision energy is partially attenuated, and the remaining energy further expands. When the compressive stress level on the glass surface is not enough to offset the remaining energy, the crack propagates through the glass surface area. When the longitudinal crack penetrates the depth of the compressive stress layer and reaches the tensile stress layer area, the crack will rapidly expand in the tensile stress area, causing the crack to penetrate the entire glass, thereby causing the glass to break and shatter into various small pieces, as shown in Figure 1.
[0006] Non-contact surface cracking occurs when a blunt object or an object with a lower hardness than the glass collides with the glass surface. The contact surface will be squeezed, and the back of the corresponding contact point will be stretched due to the deformation of the glass. When the collision force is greater than the maximum compressive stress on its surface, the glass will be damaged, as shown in Figure 2.
[0007] Glass-ceramics with petalite and lithium disilicate as the main crystalline phases has a crystallinity of over 70wt% and a transmittance close to that of commonly used lithium aluminosilicate glass. At the same time, it can be chemically strengthened in a salt bath / molten salt to further improve its anti-extrusion, impact resistance, and drop resistance properties, and has received widespread attention in the cover industry.
[0008] At present, the research on the damage resistance of microcrystalline glass / microcrystalline cover glass with petalite and lithium disilicate as the main crystal phases mainly focuses on improving CT and DOL_0, and improving the damage resistance of glass by suppressing cracking on the contact surface. There is less research on suppressing cracking on the non-contact surface to improve the damage resistance of glass. The existing microcrystalline glass of this type has the ability to resist non-contact surface cracking and needs to be further improved.
[0009] Furthermore, current research focuses primarily on improving / optimizing the mechanical properties of this type of glass-ceramics, often overlooking other properties, such as weather resistance. Application CN111867993A mentions that after undergoing ion exchange chemical strengthening, the resulting strengthened glass products tend to exhibit low chemical durability, which can significantly impact the use of the glass products in specialized environments. According to the patent application, the solution employed to improve chemical durability involves using a specific strengthening method to control the absolute value of the maximum surface compressive stress to 1.8-2.2 times the absolute value of the maximum central tensile stress, and to control the surface CS to no more than 350 MPa.
[0010] Summary of the Invention
[0011] The present disclosure provides a strengthened glass-ceramic, wherein the strengthened glass-ceramic comprises a compressive stress layer and a tensile stress layer, wherein the main crystalline phase of the strengthened glass-ceramic comprises a petalite crystalline phase and a lithium disilicate crystalline phase, and the strengthened glass-ceramic satisfies:
[0012] Surface CS ≥ 400 MPa;
[0013] Surface CS / |CT_AV|≥17.00, |CT_AV| is the absolute value of the average tensile stress in the tensile stress layer, in MPa;
[0014] DOL_0≥0.15t, DOL_0 refers to the depth of the compressive stress layer, and t is the thickness of the strengthened microcrystalline glass.
[0015] Optionally, the surface CS of the strengthened glass-ceramics is ≥500 MPa. Optionally, the surface CS is 550-1000 MPa.
[0016] Optionally, the tempered glass-ceramics has a |CT_AV| of ≥30 MPa. Optionally, |CT_AV| is 35-60 MPa.
[0017] Optionally, in the strengthened glass-ceramics, 50.00≥surface CS / |CT_AV|≥17.00.
[0018] Optionally, in the strengthened glass-ceramics, 0.25t≥DOL_0≥0.15t.
[0019] Optionally, the strengthened glass-ceramics further satisfies: |CT_CV|≥50MPa, where |CT_CV| is the absolute value of the maximum tensile stress in the tensile stress layer.
[0020] Optionally, |CT_CV| is 55-80 MPa.
[0021] Optionally, the surface K2O concentration of the strengthened glass-ceramics is ≥7.00 wt%.
[0022] Optionally, the surface K2O concentration of the strengthened glass-ceramics is 7.00-15.00 wt%.
[0023] In some optional embodiments of the present disclosure, in the strengthened glass-ceramics, the total weight of the petalite crystal phase and the lithium disilicate crystal phase accounts for no less than 71.00 wt %.
[0024] Optionally, in the strengthened glass-ceramics, the total weight of the petalite crystal phase and the lithium disilicate crystal phase accounts for 71.00-90.00 wt %.
[0025] Optionally, in the strengthened glass-ceramics, the ratio of the petalite crystal phase to the lithium disilicate crystal phase is (0.9-1.1):1.
[0026] Optionally, in the strengthened glass-ceramics, the average grain size is ≤100 nm. Optionally, the average grain size is 10-50 nm. Optionally, the average grain size is 15-25 nm.
[0027] Optionally, the composition of the strengthened microcrystalline glass tensile stress layer includes, in percentage by mass: SiO2: 58.00-76.00%, Al2O3: 6.00-8.00%, P2O5: 2.00-3.00%, ZrO2: 4.00-6.00%, Na2O: 3.00-10.00%, Li2O: 9.00-12.00%, and B2O3: 0-3.00%.
[0028] Optionally, at a thickness of 0.7 mm, the average single-rod static compressive strength of the strengthened glass-ceramics is ≥ 400 N. Optionally, at a thickness of 0.7 mm, the average single-rod static compressive strength of the strengthened glass-ceramics is 401-500 N.
[0029] Optionally, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test under the conditions of 85°C and 85% relative humidity, and its high temperature and high humidity failure time is ≥204h. The high temperature and high humidity failure time is the time when spots or fog points that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.
[0030] Optionally, at a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height is 1.10-1.50 m.
[0031] Optionally, at a thickness of 0.7 mm, the transmittance of the strengthened micro-ceramic glass is not less than 89.00% for light with a wavelength of 550 nm.
[0032] The present disclosure also provides another strengthened glass-ceramic, wherein the strengthened glass-ceramic comprises a compressive stress layer and a tensile stress layer, wherein the strengthened glass-ceramic comprises a petalite crystal phase and a lithium disilicate crystal phase with a total weight percentage of not less than 71.00 wt %;
[0033] The strengthened glass-ceramics meets the following requirements:
[0034] Surface CS ≥ 400 MPa;
[0035] Surface CS / |CT_AV|≥17.00, |CT_AV| is the absolute value of the average tensile stress in the tensile stress layer, in MPa;
[0036] DOL_0≥0.15t, DOL_0 refers to the depth of the compressive stress layer, and t is the thickness of the strengthened glass-ceramic;
[0037] The surface K2O concentration of the strengthened glass-ceramics is ≥7.50 wt%.
[0038] Optionally, the surface CS of the strengthened glass-ceramics is ≥500 MPa. Optionally, the surface CS is 550-1000 MPa.
[0039] Optionally, the tempered glass-ceramics has a |CT_AV| of ≥30 MPa. Optionally, |CT_AV| is 35-60 MPa.
[0040] Optionally, in the strengthened glass-ceramics, 50.00≥surface CS / |CT_AV|≥17.00.
[0041] Optionally, in the strengthened glass-ceramics, 0.25t≥DOL_0≥0.15t.
[0042] Optionally, the strengthened glass-ceramics further satisfies: |CT_CV|≥50 MPa, where |CT_CV| is the absolute value of the maximum tensile stress in the tensile stress layer. Optionally, |CT_CV| is 55-80 MPa.
[0043] Optionally, the surface K2O concentration of the strengthened glass-ceramics is 7.50-15.00 wt%.
[0044] Optionally, in the strengthened glass-ceramics, the total weight of the petalite crystal phase and the lithium disilicate crystal phase accounts for 71.00-90.00 wt %.
[0045] Optionally, in the strengthened glass-ceramics, the ratio of the petalite crystal phase to the lithium disilicate crystal phase is (0.9-1.1):1.
[0046] Optionally, the average grain size of the strengthened glass-ceramics is ≤100 nm. Optionally, the average grain size of the strengthened glass-ceramics is 10-50 nm. Optionally, the average grain size of the strengthened glass-ceramics is 15-25 nm.
[0047] Optionally, the composition of the strengthened microcrystalline glass tensile stress layer includes, in percentage by mass: SiO2: 58.00-76.00%, Al2O3: 6.00-8.00%, P2O5: 2.00-3.00%, ZrO2: 4.00-6.00%, Na2O: 3.00-10.00%, Li2O: 9.00-12.00%, and B2O3: 0-3.00%.
[0048] Optionally, at a thickness of 0.7 mm, the average single-rod static compressive strength of the strengthened glass-ceramics is ≥ 400 N. Optionally, at a thickness of 0.7 mm, the average single-rod static compressive strength of the strengthened glass-ceramics is 401-500 N.
[0049] Optionally, the tempered microcrystalline glass is subjected to a high temperature and high humidity failure test under the conditions of 85°C and 85% relative humidity, and its high temperature and high humidity failure time is ≥204h. The high temperature and high humidity failure time is the time when spots or fog points that cannot be wiped off appear on the tempered microcrystalline glass under the corresponding high temperature and high humidity conditions.
[0050] Optionally, at a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height is 1.10-1.50 m.
[0051] Optionally, at a thickness of 0.7 mm, the transmittance of the strengthened micro-ceramic glass is not less than 89.00% for light with a wavelength of 550 nm.
[0052] The present disclosure also provides a glass device, wherein the glass device is made of any of the above-mentioned strengthened micro-ceramics.
[0053] The present disclosure further provides an electronic device, comprising a cover, wherein the cover comprises the tempered micro-ceramic glass as described in any one of the above items.
[0054] Optionally, the electronic device includes but is not limited to at least one of a mobile phone, a display, a tablet computer, an electronic watch, a smart wearable device, and a television. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.
[0056] Figure 1 is a schematic diagram of the contact surface breakage of strengthened glass-ceramics.
[0057] FIG2 is a schematic diagram of the non-contact surface breakage of the strengthened glass-ceramics.
[0058] FIG3 is a FSM-6000 test diagram of Example 1 of the present disclosure.
[0059] FIG4 is a DSC test curve diagram of Example 1 of the present disclosure.
[0060] FIG5 is an XRD result diagram of Example 1 of the present disclosure.
[0061] FIG6 is a diagram showing the transmittance test results of Example 1 of the present disclosure.
[0062] Figure 7 is a picture of the sample of Comparative Example 4 in a high temperature and high humidity environment for 24 hours.
[0063] FIG8 is a picture of a sample in a high temperature and high humidity environment for 240 hours according to Example 1 of the present disclosure.
[0064] Figure 9 is a picture of the sample of Comparative Example 3 in a high temperature and high humidity environment for 240 hours. DETAILED DESCRIPTION
[0065] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0066] Glossary and test methods:
[0067] As used herein, the term "glass-ceramics", also known as glass-ceramics, is a type of solid composite material containing both a glass phase and a crystal phase (also known as a microcrystalline phase or a crystalline phase) prepared by targeted and controlled crystallization of a substrate glass.
[0068] As used herein, the term "strengthened glass-ceramics" refers to the solid composite material obtained by chemically strengthening glass-ceramics. During high-temperature chemical strengthening, alkali metal ions with larger ionic radii (such as potassium and sodium ions) in the salt bath / molten salt replace alkali metal ions with smaller ionic radii (such as sodium and lithium ions) in the glass-ceramics, resulting in a volume difference in the exchanged ions and compressive stress on the surface of the glass-ceramics.
[0069] As used herein, the term "surface CS" refers to surface compressive stress / surface compressive stress. After chemical strengthening of the glass-ceramics / glass-ceramics, the alkali metal ions with a smaller surface radius are replaced by alkali metal ions with a larger radius. Due to the crowding effect of the alkali metal ions with a larger radius, compressive stress is generated on the surface of the glass-ceramics, which is called surface compressive stress.
[0070] As used herein, the term “DOL_0” refers to the depth of the compressive stress layer, also known as the compressive stress layer depth, and refers to the distance from any surface of the glass to a position close to the surface where the compressive stress is zero.
[0071] As used herein, the term “|CT_AV|” refers to the absolute value of the average tensile stress in the tensile stress layer, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer.
[0072] As used herein, the term “|CT_CV|” refers to the absolute value of the maximum tensile stress, specifically the absolute value of the maximum value among all tensile stresses in the tensile stress layer.
[0073] As used herein, the thickness of glass is determined by micrometer testing. The change in thickness of glass-ceramics before and after chemical strengthening is very small and can be ignored.
[0074] As used herein, surface KO concentration is defined as the mass of KO divided by the total mass of oxides, where the total mass of oxides includes oxides such as SiO2, Al2O3, P2O5, ZrO2, Na2O, and KO that can be accurately measured by XRF, and excludes the content of oxides such as Li2O and B2O3 that cannot be accurately measured by XRF. XRF testing uses a standardless method, and the mass of elements with atomic numbers 6 and below or their oxides in the glass is not measured. That is, the total mass of oxides in the calculation of KO concentration derived from XRF testing in this disclosure does not include the mass of elements with atomic numbers 6 and below or their oxides in the glass.
[0075] As used herein, the term "refractive index" refers to the ratio of the speed of light in a vacuum to the speed of light in the medium.
[0076] As used herein, the term "SOC" refers to the photoelastic coefficient. Photoelasticity primarily refers to the anisotropic birefringence of a transparent material when subjected to stress. By measuring the photoelastic coefficient and birefringence, the residual stress (MPa) within the material can be determined.
[0077] Transmittance was measured using a UV2600 visible light spectrophotometer (Shimadzu). In the Examples and Comparative Examples of this disclosure, the transmittance of the glass-ceramics at 550 nm was the average transmittance of multiple glass samples from the same batch measured at 550 nm. At least five samples from each batch of glass-ceramics were tested.
[0078] XRD testing method: Glass-ceramics sheets were ground into fine glass powder with a particle size of less than 75 μm. The powder was then tested using an X-ray diffractometer (Shimadzu XRD_6000) within a diffraction angle range of 2θ = 10°-50°, a scanning speed of 6° / min, an operating voltage of 40 kV, and an operating current of 30 mA to obtain the XRD diffraction peak curve. The XRD diffraction data was then analyzed using specialized processing software to obtain data such as crystal content / crystalline phase content and average grain size.
[0079] The average grain size (average grain size) is obtained by calculating the average grain size using the Scherrer formula D = Kλ / (βcosθ) for the XRD test results, where λ is the X-ray wavelength, β is the peak half-height width, and K = 0.89.
[0080] The crystal content / crystalline phase content is determined by testing a glass-ceramic sample using an X-ray diffractometer (Shimadzu XRD-6000). The RAW format of the X-ray diffractometer results is then imported into Rietveld X-ray diffraction data refinement software (such as Gsas, Fullprof, or Maud) for fitting and calculation. The crystal content / crystalline phase content of the glass-ceramic sample is calculated as the ratio of the fitted crystalline phase peak area to the fitted total peak area.
[0081] The differential scanning calorimetry (DSC) test method is as follows: the sample is ground into powder and then passed through a 200-mesh sieve; the test conditions are: room temperature to 1100°C, with a heating rate of 10°C / min; the test instrument is a Mettler-Toledo TGA / DSC3+ thermogravimetric and synchronous thermal analyzer.
[0082] The surface K2O concentration of the strengthened microcrystalline glass disclosed in the present invention was measured by an X-ray fluorescence spectrometer (XRF). The equipment model used was Thermo Scientific ARL PERFORM'X, the target material was Rh (rhodium), the light tube voltage was 40kW, the current was 60mA, the collimator was 0.15, the crystal was LiF200, the detector was FPC, the test range was a 29mm circle, and the analysis software was UniQuant standardless analysis. Standardless testing was used during the XRF test, and the mass of elements with atomic numbers 6 and below or their oxides in the glass was not tested. That is, when calculating the K2O concentration obtained by the XRF test in the present disclosure, the total mass of the oxide does not include the mass of elements with atomic numbers 6 and below or their oxides in the glass.
[0083] Surface compressive stress (surface CS) test conditions: using FSM-6000 from Orihara, Japan, light source wavelength of 596 nm, SOC = 25.5 (nm / cm) / MPa, refractive index = 1.54.
[0084] Test conditions for |CT_AV|, DOL_0, and |CT_CV|: Tested using Orihara's SLP-2000, with a light source wavelength of 518 nm, SOC = 25.5 (nm / cm) / MPa, refractive index = 1.54, and exposure time: 300 usec.
[0085] When testing surface CS, |CT_AV|, DOL_0, and |CT_CV|, apply a drop of the corresponding refractive fluid to the corresponding stress gauge. Then, clean the tempered glass-ceramic and place it on the test path to measure the values. The refractive index of the refractive fluid used in the SLP-2000 is 1.51, while that used in the FSM-6000 is 1.72.
[0086] Average sandpaper drop height: The value obtained by dividing the sum of the sandpaper drop heights measured for multiple glass samples by the number of samples tested. It is used to characterize the glass's resistance to contact surface cracking. At least 10 samples are taken from each batch for testing. The average sandpaper drop height is Where n is the number of glass samples tested in each batch, and hi is the sandpaper drop resistance height of a single sample tested.
[0087] Among them, the test method for a single sample's resistance to sandpaper drop height is:
[0088] Step 1: Place the glass sample to be tested, which is 158.8mm x 72.8mm x 0.7mm in length, width and thickness, on the front of a 200g model machine.
[0089] Step 2: Place the model phone on a Green Figure LT-SKDL-CD drop machine with the glass sample facing the sandpaper. Drop it from a certain drop height, impacting the 120-grit sandpaper directly below the model phone, to simulate a normal mobile phone drop.
[0090] If the glass sample does not break, the drop height of the model machine is increased in a certain pattern. For example, the drop height starts from 0.4m and the sample is dropped once. If it does not break, the drop height is increased by 0.1m each time until the glass sample breaks.
[0091] Step 3: Record the last drop height of the glass sample when it breaks as the sandpaper drop height. For example, if the drop height when it breaks is 0.5m, the sandpaper drop height of the sample is 0.4m.
[0092] The average single-rod static compressive strength test method is to place the tempered glass-ceramic on the bottom ring of a tensile testing machine (LT_850A), start the test software, set the extrusion rod speed to 50mm / min, click Start Test, and the software will automatically read the force (N) required to break the glass. Ten pieces of glass are tested each time, and the average value is calculated to demonstrate resistance to non-contact cracking.
[0093] The high-temperature, high-humidity failure time test method is to use a QTH_80C full-scale temperature and humidity alternating test chamber for testing. Every 12 hours, the glass sample is removed and observed, and the glass surface is wiped with a dust-free cloth to observe for the appearance of indelible spots or fog spots. The time when these indelible spots or fog spots appear is the high-temperature, high-humidity failure time, which is used to characterize weather resistance. If the sample exhibits indelible spots or fog spots during this observation, but did not exhibit these during the previous observation, the time the glass sample was placed in the test chamber is calculated based on the time of the current observation and recorded as the high-temperature, high-humidity failure time for that test sample.
[0094] One embodiment of the present disclosure provides a strengthened microcrystalline glass, a glass device, and an electronic device. The strengthened microcrystalline glass overcomes to a certain extent the defect of the microcrystalline glass in the prior art that its resistance to non-contact surface cracking needs to be improved. It has excellent resistance to non-contact surface cracking and excellent resistance to contact surface cracking.
[0095] The inventors have found that: the surface CS is closely related to the ability of glass to resist non-contact surface cracking. The reduction of surface CS will lead to a reduction in the ability of glass to resist non-contact surface cracking, which can easily lead to non-contact surface cracking and damage to the glass. In this field, how to improve the ability of this type of microcrystalline glass to resist non-contact surface cracking while ensuring other excellent properties of microcrystalline glass, such as resistance to contact surface cracking (such as resistance to sandpaper drop) and weather resistance, is an urgent problem to be solved. The inventors further studied and proposed the technical solution of the present disclosure. One embodiment of the present disclosure provides a strengthened microcrystalline glass with excellent resistance to non-contact surface cracking, the strengthened microcrystalline glass has a compressive stress layer formed by chemical strengthening on the surface, and has a tensile stress layer inside that can achieve force balance with the compressive stress layer, that is, the strengthened microcrystalline glass includes a compressive stress layer and a tensile stress layer, the main crystalline phase of the strengthened microcrystalline glass includes a petalite crystalline phase and a lithium disilicate crystalline phase, and the strengthened microcrystalline glass satisfies:
[0096] Surface CS ≥ 400 MPa;
[0097] Surface CS / |CT_AV|≥17.00, |CT_AV| is the absolute value of the average tensile stress in the tensile stress layer, in MPa;
[0098] DOL_0≥0.15t, DOL_0 refers to the depth of the compressive stress layer, and t is the thickness of the strengthened microcrystalline glass.
[0099] The above-mentioned technical solution disclosed in the present invention provides a strengthened microcrystalline glass having a specific surface CS and a ratio of surface CS to |CT_AV|, and DOL_0 within the above-mentioned specific range, so that the strengthened microcrystalline glass has a special stress structure. This stress structure enables it to have a sufficient compressive stress level to suppress further expansion of cracks when it is punctured by a sharp object; it also has sufficient stress depth to prevent sudden cracks from penetrating into the tensile stress area and causing breakage; in addition, there is sufficient surface CS to suppress damage to the back side when impacted by a blunt object, thereby ensuring that the strengthened microcrystalline glass meets the requirements for resistance to contact surface cracking while having excellent resistance to non-contact surface cracking.
[0100] In some optional embodiments of the present disclosure, in the strengthened glass-ceramics, the total weight of the petalite crystal phase and the lithium disilicate crystal phase accounts for no less than 71.00 wt %.
[0101] In some optional embodiments of the present disclosure, the surface K2O concentration of the strengthened glass-ceramics is ≥7.00 wt %. Under this optional solution, the strengthened glass-ceramics can also have excellent weather resistance.
[0102] One embodiment of the present disclosure further provides a strengthened glass-ceramic having excellent crack resistance and weather resistance, wherein the strengthened glass-ceramic has a compressive stress layer formed by chemical strengthening on the surface, and has a tensile stress layer inside that can achieve force balance with the compressive stress layer. The strengthened glass-ceramic includes the compressive stress layer and the tensile stress layer, and the strengthened glass-ceramic includes a petalite crystalline phase and a lithium disilicate crystalline phase with a total weight accounting for not less than 71.00 wt %. The strengthened glass-ceramic satisfies the following conditions:
[0103] Surface CS ≥ 400 MPa;
[0104] Surface CS / |CT_AV|≥17.00, |CT_AV| is the absolute value of the average tensile stress in the tensile stress layer, in MPa;
[0105] DOL_0≥0.15t, DOL_0 refers to the depth of the compressive stress layer, and t is the thickness of the strengthened glass-ceramics;
[0106] The surface K2O concentration of the strengthened glass-ceramics is ≥7.50 wt%.
[0107] The above technical solution disclosed in the present invention provides a strengthened glass-ceramic with a specific surface CS and a ratio of surface CS to |CT_AV|, and DOL_0 within the above specific range, and with a specific suitable surface K2O concentration, so that the strengthened glass-ceramic has a special stress structure and composition, and can resist the erosion of the surface by components in water and air in high temperature and high humidity environments. The inventor believes that the reason may be K + The activity ratio of Na + Low, not easy to react with air and water, and K + Radius larger than Na + , which can block the chemical reaction between other components inside the glass and water and air, thereby ensuring that the strengthened microcrystalline glass meets the requirements of resistance to contact surface cracking while having excellent resistance to non-contact surface cracking and excellent weather resistance.
[0108] In any of the above-mentioned strengthened microcrystalline glasses disclosed in the present invention, the comprehensive performance of the strengthened microcrystalline glass is improved by the following features, as detailed below.
[0109] To further improve the weather resistance of the strengthened glass-ceramics, in an optional case, the surface K2O concentration of the strengthened glass-ceramics is 7.00-15.00wt%. Alternatively, the surface K2O concentration of the strengthened glass-ceramics is 7.50-15.00wt%. For example, the surface K2O concentration of the strengthened glass-ceramics can be any value among 7.00wt%, 7.50wt%, 8.00wt%, 8.50wt%, 9.00wt%, 9.50wt%, 10.00wt%, 10.50wt%, 11.00wt%, 11.50wt%, 12.00wt%, 13.00wt%, 14.00wt%, or 15.00wt%, and any value between adjacent values.
[0110] Optionally, in the strengthened glass-ceramics, the total weight ratio of the petalite crystal phase and the lithium disilicate crystal phase may be, for example, 71.00-90.00 wt%, 75.00-85.00 wt% or 78.00-82.00 wt%.
[0111] In some embodiments, the surface CS of the strengthened glass-ceramics is ≥500MPa, for example, it can be 500-1200MPa, such as any value of 500MPa, 550MPa, 600MPa, 650MPa, 700MPa, 750MPa, 800MPa, 850MPa, 900MPa, 950MPa, 1000MPa, 1200MPa and any value between adjacent values. The surface CS of the strengthened glass-ceramics is within the above range, so that the resistance of the strengthened glass-ceramics to non-contact surface cracking is stronger. Optionally, the surface CS is 550-1000MPa. Optionally, the surface CS is 810-900MPa. In the optional scheme disclosed herein, when a blunt object contacts the glass-ceramics, its impact force preferentially offsets the surface CS, and due to the high surface CS, the back side (i.e., the non-contact surface) will undergo smaller deformation, thereby further improving the resistance of the strengthened glass-ceramics to non-contact surface cracking.
[0112] In some embodiments, the |CT_AV| of the strengthened glass-ceramics is ≥30MPa, for example, it can be 30-80MPa, such as any value among 30MPa, 35MPa, 40MPa, 45MPa, 50MPa, 55MPa, 60MPa, 65MPa, 70MPa, 75MPa, 80MPa and any value between adjacent values. The |CT_AV| of the strengthened glass-ceramics is within the above range, so that the strengthened glass-ceramics has a stronger ability to resist contact surface cracking. Optionally, |CT_AV| is 35-60MPa. In the optional scheme disclosed in the present invention, the higher |CT_AV| can prevent further penetration of sharp objects and lateral expansion of cracks, thereby further improving the ability of the strengthened glass-ceramics to resist contact surface cracking.
[0113] In some embodiments, in the strengthened glass-ceramics, 50.00 ≥ surface CS / |CT_AV| ≥ 17.00, and can be, for example, any of 17, 18, 19, 20, 21, 22, 23, 24, 25, 30, 35, 40, 45, and 50, or any value between adjacent values. When surface CS / |CT_AV| is within the above range, the strengthened glass-ceramics exhibits high resistance to non-contact surface cracking. Alternatively, surface CS / |CT_AV| is between 18 and 23. Under this alternative solution, the stress structure of the strengthened glass-ceramics is more suitable for improving resistance to non-contact surface cracking to an even better level.
[0114] Alternatively, 0.25t ≥ DOL_0 ≥ 0.15t, for example, 0.15t-0.25t, such as any value among 0.15t, 0.16t, 0.17t, 0.20t, 0.22t, 0.23t, and 0.25t, as well as any value in between. In this alternative, the appropriate DOL_0 is compatible with the thickness t, preventing sudden cracks from penetrating the compressive stress region directly into the tensile stress region when a sharp object is inserted, leading to shattering. This allows the stress layer of the strengthened glass-ceramic to focus more on resisting contact surface cracking.
[0115] In some embodiments of the present disclosure, the strengthened glass-ceramics further satisfies the following requirement: |CT_CV| ≥ 50 MPa, where |CT_CV| is the absolute value of the maximum tensile stress in the tensile stress layer. This optional solution provides the strengthened glass-ceramics with a more optimal tensile stress layer distribution, thereby further enhancing the resistance to contact surface cracking.
[0116] Optionally, |CT_CV| is 55-80 MPa.
[0117] In some embodiments, in the strengthened glass-ceramics, the ratio of the petalite crystal phase to the lithium disilicate crystal phase is (0.9-1.1):1. In the solution of the present disclosure, the ratio of the petalite crystal phase to the lithium disilicate crystal phase is within the above range, so that the main crystal phase is reasonably distributed, which is more conducive to giving full play to the role of the strengthened glass-ceramics in resisting non-contact surface cracking. Optionally, the ratio of the petalite crystal phase to the lithium disilicate crystal phase is 0.90-0.99:1. Optionally, in the strengthened glass-ceramics, the average grain size is ≤100nm. Optionally, the average grain size is 10-50nm. Optionally, the average grain size is 15-25nm. The present disclosure has grains of suitable size, which makes the glass more transparent while ensuring strength.
[0118] In some optional embodiments of the present disclosure, the composition of the strengthened glass-ceramics tensile stress layer includes, by mass percentage, SiO2: 58.00-76.00%, Al2O3: 6.00-8.00%, P2O5: 2.00-3.00%, ZrO2: 4.00-6.00%, Na2O: 3.00-10.00%, Li2O: 9.00-12.00%, and B2O3: 0-3.00%. In this optional solution, the composition of the strengthened glass-ceramics is more conducive to forming the aforementioned specific stress distribution, as well as high transparency and intrinsic strength.
[0119] In the composition of the present disclosure, the functions of each element are as follows:
[0120] SiO2, as a former oxide of the glass network, is an indispensable component constituting the glass network structure, but excessive SiO2 can increase the viscosity of the glass, causing the problem of difficulty in glass melting. In the crystallization process, SiO2, as an important component of petalite and lithium disilicate, is also indispensable. The inventors have found that when SiO2 content is controlled within the above range, the forming and crystallization effects of the glass are better. Wherein, the content of SiO2 can, for example, be 60.00-75.00wt%, 62.00-72.00wt% or 65.00-70.00wt%, such as any value among 58.00wt%, 60.00wt%, 63.00wt%, 65.00wt%, 68.00wt%, 70.00wt%, 72.00wt%, 75.00wt%, 76.00wt% and any value between adjacent values.
[0121] Al2O3 is an important component of petalite and the primary component controlling the crystal phase ratio and grain size. Al2O3 also facilitates ion exchange during the strengthening process. However, excessive Al2O3 also tends to increase the viscosity of the glass. The inventors have discovered that controlling the Al2O3 content within the aforementioned range improves various product properties. The Al2O3 content can, for example, be 6.50-7.50 wt%, 6.80-7.20 wt%, or 6.90-7.10 wt%, such as any of 6.00 wt%, 6.50 wt%, 7.00 wt%, 7.50 wt%, and 8.00 wt%, and any values therebetween.
[0122] In the present disclosure, P2O5 is an essential component as an auxiliary nucleating agent. When its content is too little or too much, the crystallization effect is poor and the resulting glass-ceramics are not transparent enough. Therefore, P2O5 is controlled to be within the above range. The content of P2O5 can be, for example, 2.10-2.90wt%, 2.30-2.70wt% or 2.40-2.60wt%, such as any value among 2.00wt%, 2.20wt%, 2.50wt%, 2.70wt%, 2.90wt%, 3.00wt% and any value between adjacent values.
[0123] In the present disclosure, ZrO2 serves as the primary nucleating agent, reducing grain size. However, excessively high ZrO2 content increases glass melting difficulty and results in the formation of a large amount of white precipitate. Therefore, the ZrO2 content is controlled within the aforementioned range. The ZrO2 content can be, for example, 4.40-5.60 wt%, 4.80-5.30 wt%, or 4.90-5.10 wt%, such as any of 4.00 wt%, 4.20 wt%, 4.50 wt%, 5.00 wt%, 5.50 wt%, and 6.00 wt%, or any value therebetween.
[0124] Li2O and Na2O, as the external oxides of the glass network, can provide free oxygen, destroy the network structure of the glass, thereby improving the viscosity of the glass, promoting the melting and clarification of the glass liquid, and can also exchange ions with the molten salt bath. The content of both is an important factor affecting the stress of the glass, among which Na2O has a significant effect on the increase of CS on the glass surface. In addition, Li2O is also a lithium silicate (Li2SiO3) and petalite (LiAlSi4O 10) and other necessary chemical components for the formation of crystalline phases, but the addition of excessive Li2O and Na2O may lead to poor stability of the glass crystallization process, a significant decrease in crystallinity / crystal content, and even the precipitation of other crystalline phases. The inventors have found through a large number of experiments that when the Li2O content and the Na2O content are controlled within the above-mentioned ranges, the various properties of the obtained product can meet the requirements. Wherein, the content of Na2O can, for example, be 4.00-9.00wt%, 5.00-8.00wt%, 6.00-7.00wt% or 3.00-4.00wt%, such as any value among 3.00wt%, 3.50wt%, 4.00wt%, 4.50wt%, 5.00wt%, 5.50wt%, 6.00wt%, 6.50wt%, 7.00wt%, 7.50wt%, 8.00wt%, 9.00wt%, 10.00wt% and any value between adjacent values. The content of Li2O can be, for example, 9.40-11.60 wt%, 9.80-11.20 wt% or 10.50-11.00 wt%, such as any value among 9.00 wt%, 9.50 wt%, 10.00 wt%, 10.50 wt%, 11.00 wt%, 11.50 wt%, 12.00 wt% and any value between adjacent values.
[0125] In the present disclosure, B2O3 acts as a flux to reduce the high-temperature viscosity of the glass and alleviate the melting difficulties caused by ZrO2. However, excessive B2O3 can reduce the phase separation of the glass, resulting in decreased transparency. Therefore, the B2O3 content is generally controlled within the above-mentioned range. The B2O3 content can be, for example, 0.40-2.80 wt%, 0.80-2.50 wt%, or 1.20-2.00 wt%, such as any value among 0, 0.10 wt%, 0.50 wt%, 1.00 wt%, 1.50 wt%, 2.00 wt%, 2.50 wt%, and 3.00 wt%, and any value between adjacent values.
[0126] According to the present disclosure, the average single-rod static compressive strength is used to characterize the resistance to non-contact surface cracking. Optionally, at a thickness of 0.7 mm, the average single-rod static compressive strength of the strengthened glass-ceramics is ≥ 400 N. Optionally, the average single-rod static compressive strength is 401-500 N, for example, any value among 401 N, 410 N, 420 N, 430 N, 440 N, 450 N, 460 N, 470 N, 480 N, 490 N, and 500 N, or any value between adjacent values.
[0127] According to the present disclosure, weather resistance is characterized by high temperature and high humidity failure time. Optionally, under the conditions of 85°C and 85% relative humidity, the tempered glass-ceramics is subjected to a high temperature and high humidity failure test, and its high temperature and high humidity failure time is ≥204h, optionally more than 240h. The high temperature and high humidity failure time is the time when spots or fog points that cannot be wiped off appear on the tempered glass-ceramics under the corresponding high temperature and high humidity conditions. The tempered glass-ceramics disclosed in the present disclosure has a long high temperature and high humidity failure time and excellent weather resistance.
[0128] According to the present disclosure, the average sandpaper drop height is used to characterize the resistance to contact surface cracking. Optionally, when the tempered glass-ceramics is subjected to a sandpaper drop test using 120-grit sandpaper at a thickness of 0.7 mm, the average sandpaper drop height is 1.10-1.50 m, for example, any value among 1.1 m, 1.12 m, 1.15 m, 1.18 m, 1.2 m, 1.23 m, 1.25 m, 1.28 m, 1.29 m, 1.3 m, 1.32 m, 1.35 m, 1.38 m, 1.4 m, 1.45 m, 1.5 m, and any value between adjacent values.
[0129] Optionally, at a thickness of 0.7 mm, the transmittance of the strengthened glass-ceramics is not less than 89.00% for light of 550 nm wavelength. The light transmittance of the strengthened glass-ceramics disclosed in the present invention is high and can meet market demand.
[0130] The present disclosure also provides a glass device, wherein the glass device is made of any of the aforementioned strengthened micro-ceramics.
[0131] The glass device disclosed herein may be regular or irregular, and may be manufactured according to requirements.
[0132] The present disclosure also provides an electronic device, comprising a cover, wherein the cover comprises any of the aforementioned strengthened micro-ceramic glasses.
[0133] The electronic devices disclosed herein include but are not limited to at least one of a mobile phone, a display (such as a car display, an aircraft display, etc.), a tablet computer, an electronic watch, a smart wearable (such as a smart bracelet, a smart watch, and smart glasses), and a television.
[0134] In the electronic device of the present disclosure, a layer may or may not be provided on the surface of the cover.
[0135] In the present disclosure, there is no limitation on the thickness of the strengthened glass-ceramics, and the thickness of the strengthened glass-ceramics can be selected according to demand. For example, the thickness of the strengthened glass-ceramics can be 0.2-5 mm.
[0136] The present disclosure has a wide range of optional methods for preparing any of the above-mentioned strengthened microcrystalline glasses. As long as the required conditions such as the above-mentioned stress structure characteristics are met, it can ensure that the strengthened microcrystalline glass has both excellent resistance to contact surface cracking and excellent resistance to non-contact surface cracking as well as excellent weather resistance.
[0137] Optionally, the present disclosure further provides a method for preparing the strengthened microcrystalline glass, comprising: preparing substrate glass, nucleation treatment, crystallization treatment, and chemical strengthening treatment.
[0138] In some optional embodiments, the process for preparing the substrate glass includes: mixing raw materials, optionally adding a clarifier, melting, forming and cooling, and then annealing and cooling. Optionally, after annealing, cooling to room temperature to obtain the substrate glass.
[0139] Those skilled in the art can select the conditions for mixing the raw materials according to their needs. Optionally, the mixing time of the raw materials is more than 30 minutes.
[0140] In the present disclosure, those skilled in the art can select the type (such as NaCl) and dosage of the clarifier according to their needs without any creative effort.
[0141] Optionally, the melting conditions include: a temperature of 1550-1650° C. and a time of more than 5 hours.
[0142] Optionally, the final cooling temperature of the forming cooling is 700-900°C.
[0143] Optionally, the annealing conditions include: a temperature of 400-500° C. and a time of 12-240 hours.
[0144] In some optional embodiments, the nucleation treatment conditions include: a nucleation temperature of 500-700°C and a nucleation treatment time of 10-1440 minutes, and optionally, a nucleation treatment time of 50-350 minutes. The nucleation treatment time herein refers to the time after heating to the set nucleation temperature at a certain heating rate and then holding the temperature.
[0145] Optionally, the conditions of the nucleation treatment further include: heating to the nucleation temperature at a heating rate of 1-50°C / min, optionally 5-30°C / min.
[0146] In some optional embodiments, the crystallization treatment conditions include: a crystallization temperature of 600-750°C and a crystallization treatment time of 5-1440 minutes. Optionally, the crystallization treatment time is 50-350 minutes. The crystallization treatment time here refers to the time of holding the crystallization temperature after heating to the set crystallization temperature at a certain heating rate.
[0147] Optionally, the crystallization treatment conditions further include: heating to the crystallization temperature at a heating rate of 1-50°C / min. Optionally, heating to the crystallization temperature at a heating rate of 5-30°C / min.
[0148] In the present disclosure, after the crystallization treatment, steps such as shaping and polishing are further performed, and then the chemical strengthening treatment is performed. For example, the shaping and polishing steps include: shaping, cutting, and polishing a glass-ceramic sample brick (a glass-ceramic sample brick obtained by subjecting the substrate glass to nucleation and crystallization treatments) to obtain a sample of a fixed size. The sample sizes used in the following embodiments of the present disclosure include polished pieces with length, width, and thickness of 50 mm × 50 mm × 0.7 mm and 158.8 mm × 72.8 mm × 0.7 mm.
[0149] In some optional embodiments, the chemical strengthening treatment process includes: performing a primary strengthening in a sodium-potassium molten salt, and then performing a secondary strengthening in a potassium molten salt.
[0150] Optionally, the conditions for the primary strengthening include: a primary strengthening temperature of 380-550° C., and a primary strengthening time of 1-24 h.
[0151] Optionally, the secondary strengthening conditions include: a secondary strengthening temperature of 400-500° C., and a secondary strengthening time of 5-1440 min.
[0152] Optionally, in the sodium-potassium molten salt, the content of sodium salt is 5-50wt%, and the content of potassium salt is 50-95wt%.
[0153] Optionally, the content of potassium salt in the potassium molten salt is 100 wt%.
[0154] Optionally, the sodium salt is selected from at least one of sodium nitrate, sodium sulfate, and sodium carbonate, and is preferably sodium nitrate; and the potassium salt is selected from at least one of potassium nitrate, potassium sulfate, and potassium carbonate, and is preferably potassium nitrate.
[0155] The present disclosure discloses that the strengthened microcrystalline glass having the aforementioned characteristic stress structure can be prepared through the above-mentioned strengthening process.
[0156] After research, the inventors of the present disclosure discovered that the stress structure of the prior art glass-ceramics is usually characterized by surface CS and CT, but the glass-ceramics that meet a certain conventional range of surface CS and CT have a low resistance to non-contact surface cracking and cannot meet the demand, and the relationship between surface CS, CT, etc. and the resistance to non-contact surface cracking is not clear in the prior art. It was further discovered that by making the glass-ceramics with petalite and lithium disilicate as the main crystalline phases meet specific stress characteristics, especially the surface CS / |CT_AV| at a certain level, it is possible to improve the resistance of the glass-ceramics to non-contact surface cracking while ensuring that it meets the requirements for resistance to contact surface cracking. At the same time, combined with the control of the K2O concentration on the surface of the glass-ceramics, it is also possible to solve the problem that the weather resistance of the strengthened glass-ceramics products is not excellent enough.
[0157] The present disclosure utilizes the aforementioned research findings to provide a strengthened glass-ceramic having a specific surface CS and a surface CS to |CT_AV| ratio, with a DOL_0 within the aforementioned specific range. This strengthens the glass-ceramic to possess a specific stress structure, thereby significantly enhancing the glass-ceramic's resistance to non-contact cracking while also exhibiting excellent resistance to contact cracking. Furthermore, a strengthened glass-ceramic having a specific stress structure and a surface K2O concentration within a specific range is provided, which also exhibits excellent weather resistance.
[0158] Example
[0159] The present disclosure will be described in more detail below with reference to specific embodiments.
[0160] Example 1
[0161] Strengthened glass-ceramics is prepared as follows:
[0162] 1. Sample brick melting:
[0163] According to the raw material ratio of the substrate glass (numbered C) in Table 1, 1000 g of raw material was prepared, and then mixed in a V-type mixer for 30 minutes. After mixing, 5 g of a clarifier (NaCl) was added. The raw material was then transferred to a platinum crucible and melted in a 1650°C lifting furnace for 5 hours. The raw material was then poured into a forming mold and cooled to 900°C. The raw material was then placed in a 500°C annealing furnace for annealing for 24 hours, and then cooled to room temperature with the furnace to obtain the substrate glass.
[0164] 2. Sample brick crystallization:
[0165] Transparent microcrystalline glass can be prepared by sequentially subjecting the substrate glass to nucleation treatment and crystallization treatment.
[0166] Specifically, the temperature is first raised to the nucleation temperature at a heating rate of 10°C / min for nucleation treatment; then the temperature is raised to the crystallization temperature at a heating rate of 10°C / min for crystallization treatment. The nucleation temperature, nucleation treatment time, crystallization temperature, and crystallization treatment time are shown in Table 1.
[0167] The crystal content and light transmittance of the transparent micro-ceramics obtained above were tested. The result data are shown in Table 1, and the light transmittance curve is shown in FIG6 .
[0168] 3. Sample processing:
[0169] After shaping, cutting, and polishing, glass-ceramic samples can be obtained into samples of desired dimensions, such as polished glass-ceramic sheets measuring 50 mm x 50 mm x 0.7 mm, 158.8 mm x 72.8 mm x 0.7 mm, etc. The thickness is t = 0.7 mm. The difference between the thickness of glass-ceramic sheets and that of strengthened glass-ceramic sheets obtained through chemical strengthening is very small and can be ignored.
[0170] 4. Chemical strengthening:
[0171] The polished glass-ceramics obtained above were subjected to the first step of strengthening in a sodium-potassium mixed salt bath, where sodium ions were provided by sodium nitrate and potassium ions by potassium nitrate. After the first step of strengthening, the glass-ceramics were subjected to the second step of strengthening in a pure potassium salt bath, where potassium salt was provided by potassium nitrate. Thus, strengthened glass-ceramics were obtained.
[0172] The conditions for the first step of strengthening (composition of the first strong salt bath, salt bath temperature and time) and the conditions for the second step of strengthening (composition of the second strong salt bath, salt bath temperature and time) are shown in Table 2 respectively.
[0173] The tempered glass-ceramics obtained above were tested for surface K2O concentration, surface CS, |CT_AV|, |CT_CV|, DOL_0, average sandpaper drop resistance, average single-rod static pressure strength, and high-temperature, high-humidity failure time. The results are shown in Table 2. A photo of the glass tested for surface CS is shown in Figure 3. In the high-temperature, high-humidity failure time test, a photo of a sample placed in a high-temperature, high-humidity environment for 240 hours is shown in Figure 8.
[0174] In this example, the DSC test curve of the substrate glass and the XRD diffraction test curve of the glass-ceramics are shown in Figures 4 and 5, respectively. Figure 4 shows that the substrate glass of this example has clear nucleation and crystallization temperature points, and no other impurity peaks are present in the nucleation and crystallization temperature range. Figure 5 shows that the glass-ceramics prepared in this example have good crystallinity, with small grain sizes in both phases, further demonstrating their high intrinsic strength and good transparency.
[0175] Example 2-Example 5
[0176] The method of Example 1 was followed, except that the process was carried out according to the formula and process conditions in Table 1 and Table 3. The substrate glasses of Examples 2-5 were numbered D, E, F, and G, respectively.
[0177] The corresponding crystal phase and surface K2O concentration tests and performance tests are shown in Table 1 and Table 3, respectively.
[0178] Example 6
[0179] The method of Example 5 was followed, except that the process conditions in Table 3 were followed and the base glass formula was the same as that of Example 5.
[0180] The corresponding performance tests are shown in Table 3.
[0181] Comparative Example 1-Comparative Example 2
[0182] The method of Example 1 was referred to, except that the substrate glass formulations and process conditions in Tables 1 and 2 (the substrate glasses of Comparative Examples 1-2 were numbered A and B) were used.
[0183] The corresponding crystal phase test and performance test results are shown in Table 1 and Table 2 respectively.
[0184] Comparative Example 3-Comparative Example 5
[0185] The method of Example 1 was used, except that the process conditions in Table 2 were followed, and other conditions such as the base glass formula (base glass numbered C) were the same as those in Example 1.
[0186] The corresponding performance test results are shown in Table 2. In the high temperature and high humidity failure time test, Figure 7 is a picture of the strengthened micro-ceramics of Comparative Example 4 after 24 hours in a high temperature and high humidity environment, and Figure 9 is a picture of the strengthened micro-ceramics of Comparative Example 3 after 240 hours in a high temperature and high humidity environment.
[0187] Table 1
[0188] It can be seen from Table 1 that these base glass formulas numbered A, B, C to G can all be processed into microcrystalline glass with high crystallinity and good transmittance through certain nucleation and crystallization treatments. It can be seen from Table 1 that when the Na2O content is less than 3wt%, the surface CS, surface K2O concentration, and average single-rod static pressure strength of the corresponding products in Table 2 are all low; when the Na2O content is greater than 4wt%, the increase in Na2O content will lead to a partial decrease in crystallinity. The surface CS of the corresponding products in Table 3 below fluctuates between 800-900MPa, and the average single-rod static pressure strength fluctuates between 400-500N. Therefore, the Na2O content scheme disclosed in the present invention can ensure that the resulting microcrystalline glass has a higher degree of crystallinity, which is more conducive to the intrinsic strength of the product.
[0189] Table 2
[0190] It can be seen from the comparative examples and Example 1 in Table 2 that the disclosed solution of Example 1, which satisfies the conditions of surface CS ≥ 400 MPa, surface CS / |CT_AV| ≥ 17, and DOL_0 / t ≥ 0.15, has an average anti-sandpaper drop height and an average single-rod static pressure strength at a higher level, indicating that it can obtain better resistance to contact surface cracking and resistance to non-contact surface cracking. However, the comparative examples that only meet one of the above three conditions cannot take into account both resistance to non-contact surface cracking and resistance to contact surface cracking. Furthermore, the present disclosure also satisfies Example 1 in which the K2O concentration on the sample surface is greater than 7wt%, and its high temperature and high humidity failure time is longer, indicating that it has both excellent resistance to non-contact surface cracking and resistance to contact surface cracking, and better weather resistance.
[0191] As shown in Table 2, Comparative Example 1, Comparative Example 2, and Example 1, the surface K2O concentration of the samples obtained in Comparative Example 1 and Comparative Example 2 is ≤7wt%, the surface CS is <400MPa, the surface CS / |CT_AV| is <17, and DOL_0 / t ≥0.15. Finally, although Comparative Examples 1 and Comparative Examples 2 have good drop heights, their average single-rod static pressure strength is significantly lower than that of Example 1. In other words, the anti-contact surface cracking performance of Comparative Examples 1 and Comparative Examples 2 is comparable to that of Example 1, but their anti-non-contact surface cracking performance is significantly lower than that of Example 1 of the present disclosure, which simultaneously meets the following requirements: the sample surface K2O concentration is greater than 7wt%, the surface CS is ≥400MPa, the surface CS / |CT_AV| is ≥17, and DOL_0 / t ≥0.15.
[0192] It can be seen from Comparative Example 3 and Example 1 in Table 2 that although Comparative Example 3 meets the requirements of sample surface K2O concentration ≥ 7wt%, surface CS ≥ 400MPa, and DOL_0 / t ≥ 0.15, due to the long strengthening time, the surface CS drops to 413MPa, resulting in surface CS / |CT_AV| < 17, and its average single-rod static pressure strength decreases, that is, the resistance to non-contact surface cracking is reduced.
[0193] It can be seen from Comparative Example 4 and Example 1 in Table 2 that although Comparative Example 4 uses the same sample as Example 1 for strengthening, since Comparative Example 4 does not undergo secondary strengthening and the strengthening time is insufficient, although the average sandpaper drop resistance height is high, since it does not meet the surface CS / |CT_AV|≥17, its average single-rod static pressure strength is low, that is, the resistance to non-contact surface cracking performance is low.
[0194] It can be seen from Comparative Example 5 and Example 1 in Table 2 that although Comparative Example 5 uses the same sample as Example 1 for strengthening, since Comparative Example 5 does not undergo a single strengthening, although the average single-rod static pressure strength is high, since it does not meet DOL_0 / t≥0.15, its average sandpaper drop resistance height is low, that is, its resistance to contact surface cracking is low.
[0195] Table 3
[0196] It can be seen from Examples 1, 2, 3, 4, 5, and 6 in Tables 2 and 3 that the embodiment schemes of the present disclosure have an average sandpaper drop resistance of 1.10-1.50m, an average single-rod static pressure strength of ≥400N, and a high-temperature and high-humidity failure time of more than 240h (more than 204h), indicating that all embodiments of the present disclosure have excellent resistance to contact surface cracking and excellent resistance to non-contact surface cracking, as well as excellent weather resistance. By comparing Figures 7 and 8, it can be seen that the weather resistance of the strengthened microcrystalline glass using the scheme of the present disclosure is significantly better. Although it can be seen from Figure 9 that the weather resistance of Comparative Example 3 is similar to Figure 8 of Example 1 of the present disclosure, its resistance to non-contact surface cracking is significantly worse than that of the present disclosure.
[0197] The above describes in detail the optional embodiments of the present disclosure, but the present disclosure is not limited thereto. Within the technical concept of the present disclosure, various simple variations of the technical solution of the present disclosure can be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as the contents disclosed by the present disclosure and fall within the scope of protection of the present disclosure. Industrial Applicability
[0198] The present disclosure provides a strengthened microcrystalline glass, glass devices and electronic devices with excellent single-body strength and excellent drop resistance. The strengthened microcrystalline glass of the present disclosure has excellent resistance to non-contact surface cracking, as well as excellent resistance to contact surface cracking and excellent weather resistance, and therefore has excellent practical properties.
Claims
1. A strengthened glass-ceramic, comprising a compressive stress layer and a tensile stress layer, characterized in that: The main crystalline phase of the strengthened glass-ceramics includes a petalite crystalline phase and a lithium disilicate crystalline phase, and the strengthened glass-ceramics satisfies: Surface CS ≥ 400 MPa; Surface CS / |CT_AV|≥17.00, |CT_AV| is the absolute value of the average tensile stress in the tensile stress layer, in MPa; DOL_0≥0.15t, DOL_0 refers to the depth of the compressive stress layer, and t is the thickness of the strengthened microcrystalline glass.
2. The tempered glass-ceramics according to claim 1, wherein: The surface CS of the strengthened glass-ceramics is ≥500 MPa. Optionally, the surface CS is 550-1000 MPa.
3. The tempered glass-ceramics according to claim 1 or 2, characterized in that: The |CT_AV| of the strengthened glass-ceramics is ≥30 MPa. Optionally, |CT_AV| is 35-60 MPa.
4. The tempered glass-ceramics according to any one of claims 1 to 3, characterized in that In the tempered glass-ceramics, 50.00≥surface CS / |CT_AV|≥17.
00.
5. The tempered glass-ceramics according to any one of claims 1 to 4, characterized in that: 0.25t≥DOL_0≥0.15t.
6. The tempered glass-ceramics according to any one of claims 1 to 5, characterized in that: The strengthened microcrystalline glass further satisfies the following conditions: |CT_CV|≥50MPa, where |CT_CV| is the absolute value of the maximum tensile stress in the tensile stress layer. Optionally, |CT_CV| is 55-80MPa.
7. The tempered glass-ceramics according to any one of claims 1 to 6, characterized in that: The surface K2O concentration of the strengthened glass-ceramics is ≥7.00 wt%.
8. The tempered glass-ceramics according to any one of claims 1 to 7, characterized in that: The surface K2O concentration of the strengthened glass-ceramics is 7.00-15.00 wt%.
9. The tempered glass-ceramics according to any one of claims 1 to 8, characterized in that: In the strengthened glass-ceramics, the total weight of the petalite crystal phase and the lithium disilicate crystal phase accounts for no less than 71.00 wt %.
10. The tempered glass-ceramics according to any one of claims 1 to 9, characterized in that: In the strengthened glass-ceramics, the total weight of the petalite crystal phase and the lithium disilicate crystal phase accounts for 71.00-90.00 wt %.
11. The tempered glass-ceramics according to any one of claims 1 to 10, characterized in that: In the strengthened glass-ceramics, the ratio of the petalite crystal phase to the lithium disilicate crystal phase is (0.9-1.1):
1.
12. The tempered glass-ceramics according to any one of claims 1 to 11, characterized in that: In the strengthened glass-ceramics, the average grain size is ≤100 nm, and can be optionally 10-50 nm, and more preferably 15-25 nm.
13. The tempered glass-ceramics according to any one of claims 1 to 12, characterized in that: In terms of mass percentage, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2: 58.00-76.00%, Al2O3: 6.00-8.00%, P2O5: 2.00-3.00%, ZrO2: 4.00-6.00%, Na2O: 3.00-10.00%, Li2O: 9.00-12.00%, and B2O3: 0-3.00%.
14. The strengthened glass-ceramics according to any one of claims 1 to 13, characterized in that: At a thickness of 0.7 mm, the average single-rod static compressive strength of the strengthened glass-ceramics is ≥400N. Optionally, the average single-rod static compressive strength is 401-500N.
15. The strengthened glass-ceramics according to claim 7, wherein: Under the conditions of 85°C and 85% relative humidity, the tempered glass-ceramics is subjected to a high-temperature and high-humidity failure test, and its high-temperature and high-humidity failure time is ≥204h. The high-temperature and high-humidity failure time is the time when spots or fog points that cannot be wiped off appear on the tempered glass-ceramics under the corresponding high-temperature and high-humidity conditions.
16. The strengthened glass-ceramics according to any one of claims 1 to 13, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramic was subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height was 1.10-1.50 m.
17. The strengthened glass-ceramics according to any one of claims 1 to 13, characterized in that: At a thickness of 0.7 mm, the transmittance of the strengthened micro-ceramic glass is not less than 89.00% for light with a wavelength of 550 nm.
18. A strengthened glass-ceramic, comprising a compressive stress layer and a tensile stress layer, characterized in that: The strengthened glass-ceramics comprises a petalite crystal phase and a lithium disilicate crystal phase with a total weight percentage of not less than 71.00 wt %; The strengthened glass-ceramics meets the following requirements: Surface CS ≥ 400 MPa; Surface CS / |CT_AV|≥17.00, |CT_AV| is the absolute value of the average tensile stress in the tensile stress layer, in MPa; DOL_0≥0.15t, DOL_0 refers to the depth of the compressive stress layer, and t is the thickness of the strengthened glass-ceramics; The surface K2O concentration of the strengthened glass-ceramics is ≥7.50 wt%.
19. The tempered glass-ceramics according to claim 18, wherein: The surface CS of the strengthened glass-ceramics is ≥500 MPa. Optionally, the surface CS is 550-1000 MPa.
20. The tempered glass-ceramics according to claim 18 or 19, characterized in that: The |CT_AV| of the strengthened glass-ceramics is ≥30 MPa. Optionally, |CT_AV| is 35-60 MPa.
21. The strengthened glass-ceramics according to any one of claims 18 to 20, characterized in that: In the tempered glass-ceramics, 50.00≥surface CS / |CT_AV|≥17.
00.
22. The strengthened glass-ceramics according to any one of claims 18 to 21, characterized in that: In the tempered glass-ceramics, 0.25t≥DOL_0≥0.15t.
23. The strengthened glass-ceramics according to any one of claims 18 to 22, characterized in that: The strengthened microcrystalline glass further satisfies the following conditions: |CT_CV|≥50MPa, where |CT_CV| is the absolute value of the maximum tensile stress in the tensile stress layer. Optionally, |CT_CV| is 55-80MPa.
24. The strengthened glass-ceramics according to any one of claims 18 to 23, characterized in that: The surface K2O concentration of the strengthened glass-ceramics is 7.50-15.00 wt%.
25. The strengthened glass-ceramics according to any one of claims 18 to 24, characterized in that: In the strengthened glass-ceramics, the total weight of the petalite crystal phase and the lithium disilicate crystal phase accounts for 71.00-90.00 wt %.
26. The strengthened glass-ceramics according to any one of claims 18 to 25, characterized in that In the strengthened glass-ceramics, the ratio of the petalite crystal phase to the lithium disilicate crystal phase is (0.9-1.1):
1.
27. The strengthened glass-ceramics according to any one of claims 18 to 26, characterized in that In the strengthened glass-ceramics, the average grain size is ≤100 nm, and can be optionally 10-50 nm, and more preferably 15-25 nm.
28. The strengthened glass-ceramics according to any one of claims 18 to 27, characterized in that In terms of mass percentage, the composition of the strengthened microcrystalline glass tensile stress layer includes: SiO2: 58.00-76.00%, Al2O3: 6.00-8.00%, P2O5: 2.00-3.00%, ZrO2: 4.00-6.00%, Na2O: 3.00-10.00%, Li2O: 9.00-12.00%, and B2O3: 0-3.00%.
29. The strengthened glass-ceramics according to any one of claims 18 to 28, characterized in that At a thickness of 0.7 mm, the average single-rod static compressive strength of the strengthened glass-ceramics is ≥400N. Optionally, the average single-rod static compressive strength is 401-500N.
30. The strengthened glass-ceramics according to any one of claims 18 to 28, characterized in that Under the conditions of 85°C and 85% relative humidity, the tempered glass-ceramics is subjected to a high-temperature and high-humidity failure test, and its high-temperature and high-humidity failure time is ≥204h. The high-temperature and high-humidity failure time is the time when spots or fog points that cannot be wiped off appear on the tempered glass-ceramics under the corresponding high-temperature and high-humidity conditions.
31. The strengthened glass-ceramics according to any one of claims 18 to 28, characterized in that At a thickness of 0.7 mm, the tempered glass-ceramic was subjected to a sandpaper drop resistance test using 120-grit sandpaper, and the average sandpaper drop resistance height was 1.10-1.50 m.
32. The strengthened glass-ceramics according to any one of claims 18 to 28, characterized in that At a thickness of 0.7 mm, the transmittance of the strengthened micro-ceramic glass is not less than 89.00% for light with a wavelength of 550 nm.
33. A glass device, characterized in that: The glass device is made of the strengthened micro-ceramic glass according to any one of claims 1 to 17 or claims 18 to 32.
34. An electronic device comprising a cover, characterized in that: The cover comprises the strengthened glass-ceramic according to any one of claims 1 to 17 or claims 18 to 32.
35. The electronic device according to claim 34, characterized in that The electronic device includes at least one of a mobile phone, a display, a tablet computer, a smart wearable device, and a television.